Food and Livestock Sustainability in the Modern Era: Ketahanan Pangan dan Keberlanjutan Peternakan di Era Modern - Azis, Arif Rahman; Hamka, Muhammad Subhan; Bilyaro, Woki; Dani, Muhammad (BPFP Universitas Bengkulu, 2024)
The article delves into the intricate relationship between food security and livestock sustainability in today's world. With the global population on the rise and evolving consumption patterns, the livestock sector is tasked with the dual challenge of meeting the growing demand for animal protein while minimizing environmental impacts. By conducting a thorough review of literature and analyzing recent case studies, this research investigates the crucial role of livestock farming in global food security and the sustainability hurdles it confronts. Key findings indicate that technological advancements like precision livestock farming, integrated food system approaches, and circular economy concepts hold promise as solutions to enhance production efficiency and decrease environmental impacts. Additionally, the article underscores the significance of effective policies, good governance, and shifts in consumer consumption patterns in propelling the transition towards more sustainable livestock systems. In conclusion, achieving a balance between food security and livestock sustainability necessitates a comprehensive approach that integrates technological innovation, appropriate policies, and collaborative efforts across sectors. This research offers valuable insights for policymakers, industry professionals, and researchers as they work towards establishing a sustainable, fair, and resilient food system in the modern era.